Autofluorescence: A screening test for mycotic infection in tissues - Rao Shalinee; Rajkumar Aarthi; Ehtesham Md; Prathiba D (Indian Journal of Pathology and Microbiology, 2008)
Fungal infection is a major health concern as the clinical features are not very distinctive. Lack of rapid diagnostic techniques results in delay in diagnosis, which may even culminate in a fatal outcome. The fact that many pathogenic fungal organisms autofluoresce in hematoxylin and eosin (H and E)-stained sections under ultraviolet illumination led us to evaluate the role of autofluorescence as a rapid screening technique for fungal infections. The aim of the present study was to assess the value of autofluorescence as a screening method for detecting fungi on tissue sections and to compare the results of autofluorescence with conventional histochemical stains for fungi. Hematoxylin and eosin-stained slides of mycotic lesions were examined under fluorescent microscope and the findings were compared with results of Gomori′s methenamine silver and periodic acid-Schiff stains. We found fungal autofluorescence in 63 out of 64 cases studied, with a sensitivity of 97.8% and specificity of 100% in comparison with fungal stains. This was statistically significant (P < 0.05). We conclude that autofluorescence can be used as a rapid screening method for identification of fungi in tissue sections as it does not require any other specialized staining procedure